2011
DOI: 10.1088/0004-637x/731/1/5
|View full text |Cite
|
Sign up to set email alerts
|

Production of Light-Element Primary Process Nuclei in Neutrino-Driven Winds

Abstract: We present first comparisons between Light Element Primary Process (LEPP) abundances observed in some ultra metal poor (UMP) stars and nucleosynthesis calculations based on long-time hydrodynamical simulations of core-collapse supernovae and their neutrino-driven wind. UMP star observations indicate Z≥38 elements include the contributions of at least two nucleosynthesis components: r-process nuclei that are synthesized by rapid neutron capture in a yet unknown site and LEPP elements (mainly Sr, Y, Zr). We show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
209
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(219 citation statements)
references
References 72 publications
9
209
1
Order By: Relevance
“…The work of Winteler et al (2012) showed that magneto-rotational corecollapse SN jets can reproduce the solar abundance pattern for 120 < A < 210. Moreover, Arcones & Montes (2011) argue that neutrino-driven winds, either proton-or neutron-rich, stemming from core-collapse SNe can create nuclei in the range 65 < A < 115. Despite the different sites suggested, both studies illustrated the importance of knowing Y e .…”
Section: Discussion Of Yield Predictionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The work of Winteler et al (2012) showed that magneto-rotational corecollapse SN jets can reproduce the solar abundance pattern for 120 < A < 210. Moreover, Arcones & Montes (2011) argue that neutrino-driven winds, either proton-or neutron-rich, stemming from core-collapse SNe can create nuclei in the range 65 < A < 115. Despite the different sites suggested, both studies illustrated the importance of knowing Y e .…”
Section: Discussion Of Yield Predictionsmentioning
confidence: 99%
“…Nevertheless, the conditions are still poorly constrained. A number of sites have been suggested: neutron star mergers (Freiburghaus et al 1999b;Goriely et al 2011a,b;Wanajo & Janka 2012), massive core-collapse supernovae (SNe) (Wasserburg & Qian 2000;Argast et al 2004), neutrino-driven winds from core-collapse SNe (Duncan et al 1986;Meyer 1993;Takahashi et al 1994;Woosley et al 1994;Freiburghaus et al 1999a;Wanajo et al 2001;Farouqi et al 2009Farouqi et al , 2010Arcones & Montes 2011), low-mass SNe from collapsing O-Ne-Mg cores (Wanajo et al 2003; or iron cores Sumiyoshi et al 2001). However, no consensus on the formation site has been reached.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freiburghaus et al 1999;Goriely et al 2011), while the weak r-process may come from neutrino-driven winds (e.g. Arcones & Montes 2011), or electron-capturing supernovae (SNe) collapsing on O-Mg-Ne cores (Wanajo et al 2011). A p-process contribution could also be expected from supernova winds that would facilitate for example a νp-process (Fröhlich et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The following evolution of the composition is calculated within a full reaction network [10] which includes 4053 nuclei from H to Hf including both neutron-and proton-rich isotopes [5]. Experimental reaction rates [2] are included when available.…”
Section: Methodsmentioning
confidence: 99%